The Development of Theoretical Studies of Tafsir in The Kingdom of Saudi Arabia: (Comparative Study of Tafsir Marāh Labīd, Adhwā` al-Bayān, and Shafwah At-Tafāsīr) - Muhammad Rizki Romdhon (Al-'Allāmah: Journal of Scriptures and Ulama Studies, 2024)
This study was conducted with the aim of knowing what the development of Quran interpretation in the Kingdom of Saudi Arabia is represented by Tafsir Marāh Labīd by Sheikh Nawawi, Tafsir Adhwā` al-Bayān by Sheikh al-Shinqithi, and Tafsir Shafwah at-Tafāsīr by Sheikh 'Alī ash-Shābūnī. This study uses qualitative research. This research is descriptive. This research was also conducted through library research. Based on the research conducted, it can be concluded that there has been a development in the field of interpretation in the Kingdom of Saudi Arabia both from the method of interpretation, classification of interpretation, style of interpretation and interpretation of verses.